Resource availability and competition shape pollinator trophic specialization in longleaf pine savannas - Moreno-García, Pablo; Freeman, Johanna E.; Baiser, Benjamin; Campbell, Joshua W.; Li, Daijiang (Basic and applied ecology, 2025)
Realized trophic specialization, or the food resources with which a species interacts locally, is driven by a species fundamental niche, resource availability, and competition. However, the simultaneous effects of resource availability and competition on trophic specialization have yet to be investigated in plant-pollinator networks. Here, we disentangled the effects of resource availability (i.e., blooming plant diversity and abundance), and pollinator competitor pool (i.e., pollinator species richness, and abundance of conspecific and heterospecific pollinator individuals) on pollinator trophic specialization. We used samples collected over an entire flowering season in 24 xeric pine savannas in north-central Florida, USA and evaluated the effects of plant availability and pollinator competitor pool on three aspects of trophic specialization: taxonomic specialization (pollinator selection of plant species), phylogenetic specialization (pollinator selection of plant phylogenetic lineages), and functional specialization (pollinator selection of plant functional traits). Our results show that flowering resources and the pools of pollinator competitors both influence pollinator trophic specialization. Individual pollinators reacted to higher pollinator richness by interacting with more flowering plants (i.e.,taxonomically generalist), underscoring the vulnerability of pollination systems to pollinator extinctions (i.e., pollinators visit fewer plant species when there are fewer insect competitors present). Pollinators were more specialized in communities containing many conspecific pollinators, possibly reflecting pollinator preferences. Finally, in more diverse flowering plant assemblages, pollinators were taxonomic specialists in flower visitation but phylogenetic and functional generalists, providing pollination services across diverse plant assemblages.